Efficacy of Onabotulinum Toxin A (Botox) versus Abobotulinum Toxin A (Dysport) Using a Conversion Factor (1 : 2.5) in Treatment of Primary Palmar Hyperhidrosis - Hanan Mohamed El Kahky; Heba Mahmoud Diab; Dalia Gamal Aly; Nehal Magdi Farag (Hindawi Limited, 2013)
Background. Two preparations of botulinum A toxin (BTX-A) are commercially available for the treatment of palmar hyperhidrosis (PPH): Botox (Allergan; 100 U/vial) and Dysport (Ipsen Limited; 500 U/vial), which are not bioequivalent. Results regarding an appropriate conversion factor between them are controversial. Objectives. This paper aims to compare the efficacy of Botox and Dysport in PPH using a conversion factor of 1 : 2.5. Methods. Eight patients with severe PPH received intradermal injections of Botox in one palm and Dysport in the other in the same session. Clinical assessment was performed at baseline and posttreatment for 8 months using Minor's iodine starch test, Hyperhidrosis Disease Severity Scale (HDSS), and Dermatology Life Quality Index (DLQI) test. Results. At 3 weeks, a significant decrease in sweating for both preparations was noted which was more pronounced with Dysport compared with Botox. At 8 weeks, this difference turned insignificant. Continued evaluation showed similar improvement in both palms with a nonsignificant difference. Patients with longer disease duration were more liable to relapse. Conclusion. The efficacy and safety of Botox and Dysport injections were similar using a conversion factor of 1 : 2.5. There was a trend towards a more rapid action after Dysport treatment but without significant importance.